Structure and function relationships of sugar oxidases and their potential use in biocatalysis - Sriwaiyaphram, Kanokkan; Punthong, Pangrum; Sucharitakul, Jeerus; Wongnate, Thanyaporn (The Enzymes, 2020)
Several sugar oxidases that catalyze the oxidation of sugars have been isolated and characterized. These enzymes can be classified as flavoenzyme due to the presence of flavin adenine dinucleotide (FAD) as a cofactor. Sugar oxidases have been proposed to be the key biocatalyst in biotransformation of carbohydrates which can potentially convert sugars to provide a pool of intermediates for synthesis of rare sugars, fine chemicals and drugs. Moreover, sugar oxidases have been applied in biosensing of various biomolecules in food industries, diagnosis of diseases and environmental pollutant detection. This review provides the discussions on general properties, current mechanistic understanding, structural determination, biocatalytic application, and biosensor integration of representative sugar oxidase enzymes, namely pyranose 2-oxidase (P2O), glucose oxidase (GO), hexose oxidase (HO), and oligosaccharide oxidase. The information regarding the relationship between structure and function of these sugar oxidases points out the key properties of this particular group of enzymes that can be modified by engineering, which had resulted in a remarkable economic importance.